Interdisciplinary Projects Module: An innovative experience in Social Education degree from the UPV / EHU - Itziar Rekalde Rodríguez; Begoña Martínez Domínguez; J. Inazio Marko Juanikorena (Universitat Politècnica de València, 2012)
This paper presents an innovative approach to improving teacher quality that is being developed at the Faculty of Philosophy and Educational Sciences of the UPV / EHU, taking the opportunity arose with the configuration of the new curricula for their convergence in the European Higher Education Area. It is framed in the broader context of organizational change, curriculum and cultural, that is assuming the implementation of a modular design of the new degree (Education and Social Education), working in teams coordinated and with the institutional support of the UPV. The concrete innovation is presented, describes one of the seven modules of the new degree of Social Education, and underlines the work done by the faculty team who teach the five subjects that make up the module in the two official languages: Basque and Spanish, because they must plan, develop and evaluate the interdisciplinary activity in a coordinated manner. We reflect in this paper on the potential that the modular structure offers to undertake real change in the culture of teaching practice, and how to manage key factors to ensure the transition to a teaching model active, participatory and collaborative.